Without World: Global Poetics of the Border Area: Towards An Aesthetic-Political Cartography of the Common - Matas Pons, Àlex (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
The desire to know what we call the world was translated into an imaginative effort by which a supposed whole brought together its parts and encompassed its particularities. European enlightened historiography combined this dialectic between the universal and the particular with another dialectic between the geographical and the historical. It thus succeeded in justifying its politics and economics by linking a hypothetical Western geographical center with political progress, scientific development and cultural refinement. Once the narrative of this imagination is exhausted, two alternatives emerge from the aesthetic-political sphere. The first option is related to the post-Soviet order and would promote the imagination of the “too much world” through “literary communism”, based above all on the proposals of Jacques Rancière and Jean-Luc Nancy. The second option would dissociate itself from rhetorical cosmopolitanism and promote the “cosmopolitical” imagination of the “unworldly” in order to think a universal literary hospitality, without limits or restrictions.